Comparison of the sprinting stride pattern of the World and the Lithuanian elite female sprinters - Satkunskiene, D.; Stanislovaitis, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Maximal velocity is one of the most important factors of sprint, defined by the product of the stride length and the stride rate. From the biomechanical point of view the stride rate depends on the support time and non-support time. Some studies (Man & Sprague, 1980) show that the duration of the support phase is one of the most important factors defining the rate and length of the strides and consequently maximal sprinting velocity. However, Wood (1987) suggested that the ultimate speed-limiting factor is leg recovery; braking distance - the position of the CG relative to the contact point of the foot in the forward contact phase (Mero, 1988); velocity of the foot in the front contact phase (Ito, 1992; Tidow & Wiemann, 1994) and stiffness of the support leg (Èoh & Dolenec, 2002). The purpose of this investigation was to analyse the kinematics of sprinting stride of the World elite female sprinters to identify the technical factors limiting Lithuanian elite sprinters` velocity and the interactions between these factors. Methods Twelve elite female sprinters at the 9th IAAF World Championships in Athletics (age 27.33 ± 3.7 years; 100 m result 11.61 s - 10.96 s) and three Lithuanian elite sprinters (21 ± 4.36 years and 11.70 - 11.90 s respectively) were included in the analysis. The sprinting stride was analyzed with one video camera filming the performers in the sagittal plane; 50 pictures per second were recorded. Contact time, flight time, leg recovery time, the angle of tight relative to the vertical axis and the angle of shank flexion were obtained from the video recording. Stride rate, angular displacement and velocity of tight and shank were calculated. Athletes were divided into three groups: World Championships 100 m race finalists, quarter-finalists and Lithuanian elite sprinters. The distinction of sprinting stride pattern was estimated by comparing the different groups using ANOVA/MANOVA test. An alpha level of less than 0.05 (two-tailed) was considered significant. Spearman correlation was made between 100 m race result and other variables. Results Significant differences between the sprinting stride characteristics of the groups were found: support time, support time and leg recovery time percentage of the total stride time, tight angle at the instant of take-off, range of knee flexion in braking phase and range of knee extension during push off. Table 1: Kinematics parameters (mean ± SD) of the sprinting stride for 100 m race finalists (I group), quarter-finalists (II group) and Lithuanian elite sprinters (III group) Discussion/Conclusion These results demonstrate that support time, tight angle at the instant of take-off, range of knee flexion in braking phase and range of knee extension during push off are biomechanical factors limiting Lithuanian elite sprinters velocity.